Development and virtual validation of a novel digital workflow utilising open-source smartphone based stereophotogrammetry in prosthetic rehabilitation of palatal defects - Farook, Taseef Hassan (2020)
Palatal defects are rehabilitated by fabricating maxillofacial prostheses called obturators upon plaster models obtained by taking impressions of the defect site. The models are then digitally stored using expensive and not-readily-available hardware to prevent physical damage or data loss. When required, future obturators are digitally designed using expensive proprietary software and 3D printed. The objective of this research was to utilise and validate an economic in-house smartphone based stereophotogrammetry 3D scanner (SPINS) and to evaluate its accuracy in designing prostheses using open source pipeline by a comparative study. Palatal defect models were scanned using SPINS and compared against the standard laser scanner. The parameters of comparison were mesh surface area, virtual volume, Hausdorff’s distance (HD) and Dice similarity coefficient (DSC). The acceptability threshold for HD was set to <0.5mm and DSC > 0.70. SPINS derived 3D models were then used to design digital obturators using an open source workflow. Comparison of digital obturators were made using the same parameters and compared against ‘laser scanned models with proprietary software’ and ‘laser scanned models with open source software’. There were no significant differences (P>.05) in surface area and volume when comparing SPINS vs Laser scanner, with SPINS meeting both acceptability thresholds. Mesh surface area and volume were 2.12% and 1.79% more than the laser scanner respectively. Evaluation of open source workflow against proprietary counterparts also suggested no significant differences (P>.05) in surface area and volume of the prosthetic bulbs with all groups meeting both HD and DSC acceptability thresholds. When compared against the standard proprietary procedures, open source workflow demonstrated 5.80% less area and 21.40% more volume in obturator bulbs when designed from laser scanned models. Alternatively, when developed from SPINS, open source demonstrated 6.53% less area and 15.08% more volume in obturator bulbs. From the current simulation, SPINS and open source workflow should be applied to the clinical setting for further evaluation of maxillofacial defect record keeping.